In Vitro Effect of temperature on dentin bond strength of universal adhesive systems = Efecto In Vitro de la temperatura sobre la resistencia de unión de los sistemas adhesivos universales a la dentina - Akarsu, Serdar
The aim of this study was to evaluate the shear bond strength (SBS) of two universal adhesives (Universal Single Bond and All Bond Universal) and a two-step self-etch adhesive system (Clearfil SE Bond) to dentine at various temperatures. Materials and Methods: One hundred and twenty dentin specimens were divided randomly to 12 groups, according to adhesive systems (Universal Single Bond and All Bond Universal, Clearfil SE Bond) and temperature (4ºC, 20 ºC, 36ºC, 55ºC) used. Dentin specimens were prepared (n :10, adhesives were applied, and composite cylinders were polymerized. Statistical analysis of the SBS data was performed using Two-way analysis of variance (ANOVA) and Tukey's Honestly Significant Differences post-hoc test. Results: The Clearfil SE Bond was shown to have higher SBS than the universal adhesives at all temperatures; however, there was no statistically significant difference (P>0.05). In both groups, the lowest SBS values were observed in the samples at 4°C while the highest SBS values were observed in the samples at 55°C. In this case, there was a statistically significant difference (P<0.05). Conclusions: The results suggest that the effectiveness of an adhesive may increase if it is preheated at 36°C or above before use instead of being used immediately after removal from the refrigerator or at room temperature.